Lithology and minerals identification from well logs for Mishrif Formation in Ratawi oilfield - Radhi, Farah A.; Al-Fatlawi, Omar; Kadkhodaie, Ali (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Lithology identification plays a crucial role in reservoir characteristics, as it directly influences petrophysical evaluations and informs decisions on permeable zone detection, hydrocarbon reserve estimation, and production optimization. This paper aims to identify lithology and minerals composition within the Mishrif Formation of the Ratawi Oilfield using well log data from five open hole logs of wells RT-2, RT-4, RT-5, RT-6, and RT-42. At this step, the logging lithology identification tasks often involve constructing a lithology identification model based on the assumption that the log data are interconnected. Lithology and minerals were identified using three empirical methods: Neutron-Density cross plots for lithology identification, M-N cross plots (also known as Litho-porosity cross plots) for mineral identification, and Matrix identification (MID) plots. Neutron-density cross plots show that the Mishrif formation consists of limestone with some data points tending to the dolomite line east of the field and to the sandstone line west of the field. The M-N and MID plots indicate that calcite is the major mineral for the Mishrif formation; however, quartz grows to the west of the area while dolomite increases to the east. These findings underscore the importance of integrating multiple well-log interpretation techniques to capture lithologic and mineralogical complexity, providing critical insights for reservoir management and targeted exploitation strategies in heterogeneous carbonate systems.